2017
DOI: 10.1002/jor.23387
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tibiofemoral joint space width measurements from standing CT and fixed flexion radiography

Abstract: The objective of this project was to determine the relationship between medial tibiofemoral joint space width measured on fixed-flexion radiographs and the three-dimensional joint space width distribution ona low-dose, standing CT (SCT) imaging. At the 84-month visit of the Multicenter Osteoarthritis Study, 20 participants were recruited. A commercial SCT scanner for the foot and ankle was modified to image knees while standing. Medial tibiofemoral joint space width was assessed on radiographs at fixed locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…For quantifying the tibiofemoral JS, different semi‐automatic methods have been tested on cone‐beam CT images 46, 47. High‐resolution cone‐beam CT systems with voxel size <100 µm for assessment of bone and joint health are under development 48…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For quantifying the tibiofemoral JS, different semi‐automatic methods have been tested on cone‐beam CT images 46, 47. High‐resolution cone‐beam CT systems with voxel size <100 µm for assessment of bone and joint health are under development 48…”
Section: Discussionmentioning
confidence: 99%
“…36 For quantifying the tibiofemoral JS, different semi-automatic methods have been tested on cone-beam CT images. 46,47 Highresolution cone-beam CT systems with voxel size <100 mm for assessment of bone and joint health are under development. 48 We have demonstrated that morphological analysis of the joint space performed on CT images with sufficiently high resolution is pertinent to describe indirectly tibial cartilage and meniscal impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects removed footwear prior to stepping into a foot-positioning frame;[10] the toes and medial surface of the feet were placed against vertical platforms that externally rotated the feet by 10°. The skin over the patella and anterior thighs was in direct contact with the thigh- positioning plate.…”
Section: Methodsmentioning
confidence: 99%
“…[9, 10] If this valid measurement also were found to have high reliability, then the weight-bearing 3D nature of SCT may be an attractive replacement for weight-bearing knee radiographs. [6, 810] Specifically, adequate reliability in weight-bearing JSW assessment would indicate that SCT imaging retains the advantages of knee radiography while circumventing its limitations. The purpose of this study was to determine the test-retest reliability of JSW measurements using low-dose SCT imaging acquired 2 weeks apart in order to advance knowledge regarding the potential for improving assessment of tibiofemoral OA disease status.…”
Section: Introductionmentioning
confidence: 99%
“…Although CT is established in the role of visualizing mineralized peri-articular structures such as subchondral bone (8), it has otherwise been limited when compared to radiography in the investigation of the joint space in osteoarthritis by an historic inability to image in a weight-bearing position. However, cone beam CT technology can now acquire images of the standing knee (9), meaning that there could be advantages over radiography in the assessment of JSW in a threedimensions (3-D), principally through removal of projectional variability in X-ray beam positioning, and the opportunity for a more accurate representation of JSW distribution leading to greater sensitivity in detecting disease-relevant structural changes. Although this may come with some increase in image noise, it can be achieved at much lower doses than, for example, clinical hip CT (~0.02-0.25 mSv compared to ~2.5 mSv per scan) (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%